Impaired CK1 Delta Activity Attenuates SV40-Induced Cellular Transformation In Vitro and Mouse Mammary Carcinogenesis In Vivo - Hirner, Heidrun; Günes, Cagatay; Bischof, Joachim; Wolff, Sonja; Grothey, Arnhild; Kühl, Marion; Oswald, Franz; Wegwitz, Florian; Bösl, Michael R.; Trauzold, Anna; Henne-Bruns, Doris; Peifer, Christian; et al. (PLOS ONE, 2012)
Simian virus 40 (SV40) is a powerful tool to study cellular transformation in vitro, as well as tumor development and progression in vivo. Various cellular kinases, among them members of the CK1 family, play an important role in modulating the transforming activity of SV40, including the transforming activity of T-Ag, the major transforming protein of SV40, itself. Here we characterized the effects of mutant CK1δ variants with impaired kinase activity on SV40-induced cell transformation in vitro, and on SV40-induced mammary carcinogenesis in vivo in a transgenic/bi-transgenic mouse model. CK1δ mutants exhibited a reduced kinase activity compared to wtCK1δ in in vitro kinase assays. Molecular modeling studies suggested that mutation N172D, located within the substrate binding region, is mainly responsible for impaired mutCK1δ activity. When stably over-expressed in maximal transformed SV-52 cells, CK1δ mutants induced reversion to a minimal transformed phenotype by dominant-negative interference with endogenous wtCK1δ. To characterize the effects of CK1δ on SV40-induced mammary carcinogenesis, we generated transgenic mice expressing mutant CK1δ under the control of the whey acidic protein (WAP) gene promoter, and crossed them with SV40 transgenic WAP-T-antigen (WAP-T) mice. Both WAP-T mice as well as WAP-mutCK1δ/WAP-T bi-transgenic mice developed breast cancer. However, tumor incidence was lower and life span was significantly longer in WAP-mutCK1δ/WAP-T bi-transgenic animals. The reduced CK1δ activity did not affect early lesion formation during tumorigenesis, suggesting that impaired CK1δ activity reduces the probability for outgrowth of in situ carcinomas to invasive carcinomas. The different tumorigenic potential of SV40 in WAP-T and WAP-mutCK1δ/WAP-T tumors was also reflected by a significantly different expression of various genes known to be involved in tumor progression, specifically of those involved in wnt-signaling and DNA repair. Our data show that inactivating mutations in CK1δ impair SV40-induced cellular transformation in vitro and mouse mammary carcinogenesis in vivo.